අඛණ්ඩ ගුරු අධ්‍යාපනය ලබාදීම සදහා ඇති කරන ලද ගුරු මධ්‍යස්ථානවල ක්‍රියාකාරිත්වය පිළිබඳ විමර්ශනාත්මක අධ්‍යයනයක් - අබේසිරිවර්ධන, එස්. (My University, 2004)
The teacher is one of the main factors affecting qualitative development in education. It is through teacher education that a teacher becomes a professional. The history of education in Sri Lanka indicates that teachers have been trained variously using different modes, overtime. With the introduction of education reforms in 1988, to overcome existing limitations in teacher training, a new structure was introduced for the continuing education of teachers ...